Diabetes association with self‐reported health, resource utilization, and prognosis post‐myocardial infarction. Issue 12 (4th November 2020) - Nicolau, José C.; Brieger, David; Owen, Ruth; Furtado, Remo H.M.; Goodman, Shaun G.; Cohen, Mauricio G.; Simon, Tabassome; Westermann, Dirk; Granger, Christopher B.; Grieve, Richard; Yasuda, Satoshi; Chen, Jiyan; et al.
Abstract: Background: Diabetes mellitus (DM) is associated with increased cardiovascular (CV) risk. We compared health‐related quality of life (HRQoL), healthcare resource utilization (HRU), and clinical outcomes of stable post‐myocardial infarction (MI) patients with and without DM. Hypothesis: In post‐MI patients, DM is associated with worse HRQoL, increased HRU, and worse clinical outcomes. Methods: The prospective, observational long‐term risk, clinical management, and healthcare Resource utilization of stable coronary artery disease study obtained data from 8968 patients aged ≥50 years 1 to 3 years post‐MI (369 centers; 25 countries). Patients with ≥1 of the following risk factors were included: age ≥65 years, history of a second MI >1 year before enrollment, multivessel coronary artery disease, creatinine clearance ≥15 and <60 mL/min, and DM treated with medication. Self‐reported health status was assessed at baseline, 1 and 2 years and converted to EQ‐5D scores. The main outcome measures were baseline HRQoL and HRU during follow‐up. Results: DM at enrollment was 33% (2959 patients, 869 insulin treated). Mean baseline EQ‐5D score (0.86 vs 0.82; P < .0001) was higher; mean number of hospitalizations (0.38 vs 0.50, P < .0001) and mean length of stay (LoS; 9.3 vs 11.5; P = .001) were lower in patients without vs with DM. All‐cause death and the composite of CV death, MI, and stroke were significantly higher in DM patients, with adjusted 2‐year rate ratios of 1.43 ( P < .01) and 1.55 ( P < .001), respectively. Conclusions: Stable post‐MI patients with DM (especially insulin treated) had poorer EQ‐5D scores, higher hospitalization rates and LoS, and worse clinical outcomes vs those without DM. Strategies focusing specifically on this high‐risk population should be developed to improve outcomes. Trial registration: ClinicalTrials.gov : NCT01866904 (https://clinicaltrials.gov ).